Tau Filament Self-Assembly and Structure: Tau as a Therapeutic Target - Oakley, Sebastian S.; Maina, Mahmoud B.; Marshall, Karen E.; Al-Hilaly, Youssra K.; Harrington, Charlie R.; Wischik, Claude M.; Serpell, Louise C. (Frontiers in Neurology, 2020)
Tau plays an important pathological role in a group of neurodegenerative diseases, called tauopathies, including Alzheimer’s disease, Pick’s disease, chronic traumatic encephalopathy and corticobasal degeneration. In each disease, tau self-assembles abnormally to form filaments that deposit in the brain. Tau is a natively unfolded protein that can adopt different structures in different pathological disorders. Cryo-electron microscopy has recently provided a series of structures for the core of the filaments purified from brain tissue from patients with different tauopathies and revealed that they share a common core region, while differing in their specific conformation. This structurally resolvable part of the core is contained within a proteolytically stable core region (297-391, dGAE) from the repeat domain initially isolated from AD filaments . Tau has recently become an important target for therapy. Recent work has suggested that the prevention of tau self-assembly may be effective in slowing the progression of Alzheimer’s disease and other tauopathies. Here we review the work that explores these potential mechanisms and examine model systems that permit the exploration of the mode of action of potential inhibitors.